E-training tools on dairy cattle management practices in smallholder farming systems of Eastern Africa - CGIAR Research Program on Livestock (2021)
In collaboration with Farm.ink two digital training courses have been developed for dairy farmers in East Africa. Courses were digitized using the Learn.ink platform which turns static course content into a fun and engaging web app. Users of the tool gave positive feedback during piloting, validating the approach.